2021
DOI: 10.1093/nar/gkab1152
|View full text |Cite
|
Sign up to set email alerts
|

A distinct complex of PRP19-related and trypanosomatid-specific proteins is required for pre-mRNA splicing in trypanosomes

Abstract: The pre-mRNA splicing factor PRP19 is recruited into the spliceosome after forming the PRP19/CDC5L complex in humans and the Nineteen complex in yeast. Additionally, ‘PRP19-related’ proteins enter the spliceosome individually or in pre-assemblies that differ in these systems. The protistan family Trypanosomatidae, which harbors parasites such as Trypanosoma brucei, diverged early during evolution from opisthokonts. While introns are rare in these organisms, spliced leader trans splicing is an obligatory step i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…New research shows that the interaction of Prdx1 with UCH37 attenuates the effects of UCH37 on cell migration and invasion; this interaction may be through the formation of a complex rather than the deubiquitination of UCH37 itself, but the mechanism of the two on the development of liver cancer has not yet been elucidated ( 181 ). UCH37 can also act on the RNA splicing factor PRP19 through deubiquitination ( 182 ), and their interaction can promote HCC migration and invasion ( 176 ).…”
Section: Ubiquitin C-terminal Hydrolasementioning
confidence: 99%
“…New research shows that the interaction of Prdx1 with UCH37 attenuates the effects of UCH37 on cell migration and invasion; this interaction may be through the formation of a complex rather than the deubiquitination of UCH37 itself, but the mechanism of the two on the development of liver cancer has not yet been elucidated ( 181 ). UCH37 can also act on the RNA splicing factor PRP19 through deubiquitination ( 182 ), and their interaction can promote HCC migration and invasion ( 176 ).…”
Section: Ubiquitin C-terminal Hydrolasementioning
confidence: 99%
“…16 Serine and arginine rich splicing factor 3 (SRSF3) is essential for the development of fertile oocytes, as it controls the transcriptional properties of the maternal transcriptome, and heterogeneous nuclear ribonucleoprotein H1 (hnRNPH1) governs a network of alternative splicing (AS) events in germ cells via recruitment of polypyrimidine tract binding protein 2 (PTBP2) and SRSF3. 17,18 BCAS2 is one of the components of the PRP19/CDC5L complex, 19 which plays a central role in the catalytic activation of the spliceosome, 20 and PRP19 and its related proteins are major components of the spliceosome's catalytic core RNP. 19 Previous studies have reported that loss of BCAS2 in oocytes leads to poor oocyte quality, abnormal oogenesis, and disrupted follicular development.…”
Section: Introductionmentioning
confidence: 99%
“…BCAS2 is one of the components of the PRP19/CDC5L complex, 19 which plays a central role in the catalytic activation of the spliceosome, 20 and PRP19 and its related proteins are major components of the spliceosome's catalytic core RNP 19 . Previous studies have reported that loss of BCAS2 in oocytes leads to poor oocyte quality, abnormal oogenesis, and disrupted follicular development.…”
Section: Introductionmentioning
confidence: 99%